2019
DOI: 10.1266/ggs.19-00029
|View full text |Cite
|
Sign up to set email alerts
|

Transposable elements as genetic accelerators of evolution: contribution to genome size, gene regulatory network rewiring and morphological innovation

Abstract: In the current era, as a growing number of genome sequence assemblies have been reported in animals, an in-depth analysis of transposable elements (TEs) is one of the most fundamental and essential studies for evolutionary genomics. Although TEs have, in general, been regarded as non-functional junk/selfish DNA, parasitic elements or harmful mutagens, studies have revealed that TEs have had a substantial and sometimes beneficial impact on host genomes in several ways. First, TEs are themselves diverse and thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 123 publications
1
31
0
Order By: Relevance
“…S2 ). Consistent with the previous observations, it is also interesting that the proportion of TEs is generally correlated with the genome size in mammals 51 , 52 ( Supplementary Fig. S2 ).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…S2 ). Consistent with the previous observations, it is also interesting that the proportion of TEs is generally correlated with the genome size in mammals 51 , 52 ( Supplementary Fig. S2 ).…”
Section: Resultssupporting
confidence: 90%
“…In general, different types of SINE families are distributed for each mammalian clade, such as order, sub-order, or family. 52 In megabats, the only known active SINEs are the 5S rRNA-derived MEG SINEs. 54 It should be noted that Rousettus genomes contain no more than 23,000 copies of the MEG-related SINEs, which cover 0.21% of the genome.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that up to 70%, of the human genome originates from TEs [1][2][3]. Generally, TEs are categorized as junk DNA [4]; however, many studies have shown that they have, in fact, contributed greatly to mammalian evolution [5][6][7]. Furthermore, TEs promote rearrangement of chromosomal DNA [8], and can become sources of both coding and regulatory sequences during the evolution of host genomes [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In plants, transposons play a key role in characters of agronomic interest and in their domestication. TEs contribute to genome evolution is through TE exaptation, a process whereby TEs, which usually persist by replicating in the genome, are integrated as novel host genes, which thereafter persist by conferring phenotypic benefits (Joly‐Lopez & Bureau, 2018; Nishihara, 2020; Schrader & Schmitz, 2019). Many TE‐induced mutations have been selected during plant domestication.…”
Section: The Key Role Of Tes In Agronomic Traits Of Cropsmentioning
confidence: 99%
“…To understand the role that TEs have played during evolution, it is necessary to consider both history of their discovery and their genomic activity (Lisch, 2013). In plants, as in most organisms, TEs are by far the most variable sequences of the genome; TEs are DNA sequences capable of changing their position within a genome and being mobilized between different species (Bourque et al, 2018; Huang, Burns, & Bok, 2012; Nishihara, 2020; Slotkin & Martienssen, 2007). Expansion and contraction in the number of TEs can lead to dramatic differences in chromosomes rearrangement and in genome size, especially in species where TEs constitute the most conspicuous part of DNA (Kojima, 2020; Larsen, 2018; Vicient & Casacuberta, 2017).…”
Section: Introductionmentioning
confidence: 99%